VD_FINDINFO Jug / 2012 / 24 vom 29. Juni 2011 - VD Tribunal cantonal (2011)
FIXATION DE LA PEINE, AMENDE, DISPOSITIONS PÉNALES DE LA LCR, PRÉSOMPTION D'INNOCENCE | 106 CP, 47 CP, 10 CPP, 90 ch. 1 LCR, 90 ch. 2 LCR, 93 ch. 2 LCR